2020
DOI: 10.1093/jn/nxaa198
|View full text |Cite|
|
Sign up to set email alerts
|

Placental and Cord Blood Telomere Length in Relation to Maternal Nutritional Status

Abstract: Background The uterine environment may be important for the chromosomal telomere length (TL) at birth, which, in turn, influences disease susceptibility throughout life. However, little is known about the importance of specific nutritional factors. Objectives We assessed the impact of multiple maternal nutritional factors on TL in placenta and cord blood. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
11
1
Order By: Relevance
“…However, few studies indicate a discrepancy in the results of TL in the cord blood compared to the placenta (19,57), and we found no differences in TL between the cord blood and the placenta in the current study. Meanwhile, TL in the placenta may have different responses from cord blood cells to environmental stimuli, including maternal nutritional status (17,19,33). Recently, Vahter et al have reported that maternal BMI, body fat percentage, and vitamin B 12 are inversely associated with placental TL, whereas 25 (OH) D 3 is positively associated, and no associations were observed with cord blood TL (19).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…However, few studies indicate a discrepancy in the results of TL in the cord blood compared to the placenta (19,57), and we found no differences in TL between the cord blood and the placenta in the current study. Meanwhile, TL in the placenta may have different responses from cord blood cells to environmental stimuli, including maternal nutritional status (17,19,33). Recently, Vahter et al have reported that maternal BMI, body fat percentage, and vitamin B 12 are inversely associated with placental TL, whereas 25 (OH) D 3 is positively associated, and no associations were observed with cord blood TL (19).…”
Section: Discussioncontrasting
confidence: 72%
“…As the pregnancy progresses, telomerase activity in the placenta declines, resulting in shortened TL across gestation with the shortest telomeres at term (54,55), probably due to the increasing production of mediators, particularly pro-inflammatory cytokines, neutrophil recruitment chemokines, and arachidonic acid metabolites of chorioamniotic cells in the third trimester of pregnancy (56). However, few studies indicate a discrepancy in the results of TL in the cord blood compared to the placenta (19,57), and we found no differences in TL between the cord blood and the placenta in the current study. Meanwhile, TL in the placenta may have different responses from cord blood cells to environmental stimuli, including maternal nutritional status (17,19,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have also investigated the association between maternal nutritional status and placental tissue telomere length [23 ▪ ]. They found that greater maternal body-mass index, body fat percentage, and vitamin B-12 status were associated with shorter placental relative telomere length whereas greater vitamin D levels were associated with longer placental telomere length.…”
Section: Telomeres During Pregnancymentioning
confidence: 99%